Relational Contracts and the Theory of the Firm - Baker, G.; Gibbons, R.; Murphy, K. J. (Quarterly Journal of Economics, 2002)
Relational contracts—informal agreements sustained by the value of future relationships—are prevalent within and between firms. We develop repeated-game models showing why and how relational contracts within firms (vertical integration) differ from those between (nonintegration). We show that integration affects the parties' temptations to renege on a given relational contract, and hence affects the best relational contract the parties can sustain. In this sense, the integration decision can be an instrument in the service of the parties' relationship. Our approach also has implications for joint ventures, alliances, and networks, and for the role of management within and between firms.